2022
DOI: 10.3390/ani12030282
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Marine Turtles and Welfare Improvement by Application of Environmental Enrichment Strategies

Abstract: Sea turtles perform various ecological services in several marine environments and are considered architects of the marine landscape. At present, they are endangered species due to anthropogenic threats, pollution and degradation of marine habitats. These impacts make it urgent to increase protection and conservation efforts. Protective actions include the rescue and rehabilitation of injured individuals as a result of their interactions with humans and other threats. Environmental enrichment (EE) is a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This study employs a quantitative research approach to explore the potential and impact of implementing High Order Thinking Skills (HOTS)-based learning on the enhancement of maritime environmental awareness among students in the city of Bandung. The research procedures in this study encompass the following steps: (1) examining and describing phenomena related to the elevation of maritime awareness in Indonesia and the necessity to reinforce student learning in order to cultivate such awareness based on HOTS; (2) determining the study's design and methodology; (3) conducting a literature review, distributing questionnaires, and conducting interviews; (4) processing data and presenting study findings; (5) analyzing and interpreting study findings; and (6) reporting the study results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study employs a quantitative research approach to explore the potential and impact of implementing High Order Thinking Skills (HOTS)-based learning on the enhancement of maritime environmental awareness among students in the city of Bandung. The research procedures in this study encompass the following steps: (1) examining and describing phenomena related to the elevation of maritime awareness in Indonesia and the necessity to reinforce student learning in order to cultivate such awareness based on HOTS; (2) determining the study's design and methodology; (3) conducting a literature review, distributing questionnaires, and conducting interviews; (4) processing data and presenting study findings; (5) analyzing and interpreting study findings; and (6) reporting the study results.…”
Section: Methodsmentioning
confidence: 99%
“…This progress has significantly enhanced human capacities to explore and exploit the vast potential of the seas. However, concurrently, the sustainability of the maritime environment has emerged as an increasingly pressing concern in academic discourse [3]- [5]. The intricately interconnected challenges of climate change, pollution, habitat degradation, and excessive exploitation of marine resources pose grave threats to the continuity and resilience of marine ecosystems, as well as to the overall well-being of human societies that depend on these ecosystems for sustenance and livelihood.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental enrichment (EE) is a management principle aimed at meeting the needs of the animal kept under human care, providing psychological and physiological well-being [ 1 , 2 , 3 , 4 ], and identifying and providing environmental stimuli necessary for animal well-being [ 4 , 5 , 6 , 7 ]. Various studies have shown that an enriched environment offers greater behavioural opportunities for the animal, making its behavioural repertoire more indicative of good welfare [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individual animals housed in conservation projects benefit from appropriate use of EE to develop important behavioral skills that facilitate a successful life in the wild (Rabin, 2003; Reading et al, 2013). For wild individuals spending time in captivity within a wildlife rescue center (Escobedo‐Bonilla et al, 2022; Monreal‐Pawlowsky et al, 2017) or for juvenile life stages where behavioral flexibility and diversity is influenced by environmental and social interaction (Hyvärinen & Rodewald, 2013), appropriate use of EE can preserve or develop important survival skills. As animals in wildlife rescue and rehabilitation centers are destined to be returned to the wild (if deemed fit and healthy), the performance of adaptive behaviors that ensure survival needs to continue during the animal's stay in captivity.…”
Section: Introductionmentioning
confidence: 99%